Frustration Between Preferred States of Complementary Trinucleotide Repeat DNA Hairpins Anticorrelates with Expansion Disease Propensity. Issue 10 (15th May 2023) - Xu, Pengning; Zhang, Jiahui; Pan, Feng; Mahn, Chelsea; Roland, Christopher; Sagui, Celeste; Weninger, Keith
Graphical abstract: Highlights: Trinucleotide repeat (TR) DNA is associated with over 30 neurodegenerative diseases. CAG, CTG, GTC TR hairpins favor tetraloop while GAC favors triloop configuration. CAG, CTG hairpins adopt favored loop configurations more than GAC, GTC hairpins. Interrupted (CAG) ∙ (CTG) TR hairpins frustrate strand slippage and favor cruciform. Abstract: DNA trinucleotide repeat (TRs) expansion beyond a threshold often results in human neurodegenerative diseases. The mechanisms causing expansions remain unknown, although the tendency of TR ssDNA to self-associate into hairpins that slip along their length is widely presumed related. Here we apply single molecule FRET (smFRET) experiments and molecular dynamics simulations to determine conformational stabilities and slipping dynamics for CAG, CTG, GAC and GTC hairpins. Tetraloops are favored in CAG (89%), CTG (89%) and GTC (69%) while GAC favors triloops. We also determined that TTG interrupts near the loop in the CTG hairpin stabilize the hairpin against slipping. The different loop stabilities have implications for intermediate structures that may form when TR-containing duplex DNA opens. Opposing hairpins in the (CAG) ∙ (CTG) duplex would have matched stability whereas opposing hairpins in a (GAC) ∙ (GTC) duplex would have unmatched stability, introducing frustration in the (GAC) ∙ (GTC) opposing hairpins that could encourage their resolution to duplex DNA more rapidly than in (CAG) ∙ (CTG) structures. Given that the CAG and CTG TR can undergo large, disease-related expansion whereas the GAC and GTC sequences do not, these stability differences can inform and constrain models of expansion mechanisms of TR regions.